Thiocarbonate Collectors in Pyrite Flotation - Fundamentals and Applications (6623b77e-b8f8-4b4d-b445-6e9e3ffafa48) - Ronel du Plessis; Jan D. Miller; John C. Davidtz (International Mineral Processing Congress, 2003)
Recent results from electrochemical measurements demonstrate that trithiocarbonate (TTC) collectors are more readily oxidized to their corresponding dithiolates than the dithiocarbonate/xanthate (DTC) collectors. Based on the traditional analysis of collector adsorption, trithiocarbonates might then be expected to be effective for bulk sulfide mineral flotation. Previous bench-scale flotation research had shown that TTC collectors are very effective for the flotation of copper sulfide minerals and PGM (platinum group metal) sulfide minerals. More recently, the TTC collectors were evaluated for auriferous pyrite recovery in benchscale plant scale flotation testing in the United States and in plant tests at Anglogold in South Africa. TTC collectors were also applied in bench-scale testing of a PGM ore. In each case an improved separation efficiency was realized. Fundamental studies at the University of Utah examining the effect of collector structure (functional group, -O-CS2 versus .S-CS2), specifically with respect to auriferous pyrite flotation, are in progress. The effect of collector structure was evaluated with air as well as nitrogen as the flotation gas medium. Experimental techniques utilized included electrochemically controlled contact angle measurements to evaluate mineral hydrophobicity and infrared spectroscopy to explain collector adsorption phenomena at the mineral surface.